PEMBINAAN TAHFIDZ AL-QUR’AN DI MADRASAH IBTIDAIYAH ASY-SYAR’IYAH TANGKAWANG KECAMATAN HAUR GADING KABUPATEN HULU SUNGAI UTARA - Azizah, Azizah; Syakhrani, Abdul Wahab; Susanti, Ria (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2023)
The background of this research is that the implementation of tahfidz Al-Qur'an coaching will give maximum results if the teachers/ustadz understand everything related to the coaching process itself, including in terms of the methods used in tahfidz coaching, because when the teacher has found a method the right method in memorizing and maintaining student memorization will have a significant influence so that the goals of tahfidz coaching can be achieved properly. This research focuses on the methods used by teachers in memorizing and maintaining (maintaining) the memorization of the Qur'an in their students at Madrasah Ibtidaiyah Asy-Syar'iyah Tangkawang, Haur Gading District, Hulu Sungai Utara District. This study aims to find out how to foster tahfidz Al-Qur'an related to the method of memorizing and maintaining memorization as well as the inhibiting factors in the process of fostering tahfidz Al-Qur'an in Madrasah Ibtidaiyah Asy-Syar'iyah Tangkawang, Haur Gading District, Hulu Sungai Utara Regency so that objectives of coaching can be achieved. The method used in this study is a qualitative research methodology with a descriptive approach, which produces data in the form of written or spoken words. The subjects in this study were tahfidz teachers at Madrasah Ibtidaiyah Asy-Syar'iyah Tangkawang, Haur Gading District, Hulu Sungai Utara Regency, totaling 7 people. Meanwhile, the object of this research is the process of fostering tahfidz at Madrasah Ibtidaiyah Asy-Syar'iyah Tangkawang, Haur Gading District, Hulu Sungai Utara Regency. Data collection techniques used include interviews, observation, and documentaries. While data processing techniques include data collection, data reduction, data display, and data verification, then analysis is carried out. The results of this study are: (1) Method of memorizing by: memorizing by together, memorizing by listening to the teacher's reading directly, memorizing by the teacher reading first then followed by the students, and memorizing by reading to the teacher (Deposit). (2) Methods for maintaining memorization by means of: reciting together, playing memorization in front of friends and teachers, connecting verses and reciting surahs, and repeating memorization by playing the MP3 Al-Qur'an. (3) Obstacle factors encountered include: some children cannot recite the Koran and are not fluent in reading the Qur'an, difficulties in memorizing, lack of interest and motivation causing children to be lazy, mistakes in reading that do not match the script and length, and lack of facilities and infrastructure in supporting tahfidz learning.